Closing “The Mediterranean Cemetry”: whether the European agenda on migration (immediate action) aimed at curbing the Africa-EU migration “crisis” is International Law compliant? - Mandela, Walter (Department of Public Law, 2019)
The aim of the thesis is to establish whether the EAM (Immediate Action), formulated to curb the Africa-EU irregular migration “crisis” complies with international law. The thesis commences by arguing that migration today is a bastion of state sovereignty though fettered to a very limited extent by human rights, international law and states’ inter-dependence. The thesis then discusses the right to asylum and the principle of non-refoulement under international law. This is followed by a discussion on the EU as “sui generis” supra national entity that champions human rights and the rule of law globally followed by a review of its “sui generis” immigration law and rules under which the EU and member states share competence. Fundamental terminologies in the migration discourse: Migrants, Irregular Migrants, Refugees and Asylum Seekers are defined. A critique of The Refugee Convention4 is done, revealing its parochial, Eurocentric, racist, sexist nature and incompatibility with recent human rights developments; factors that to a large extent make it archaic and divorced from the realities of today’s refugee dynamics yet the Convention is the centrepiece of international refugee protection today. The thesis then interrogates the Africa-EU irregular mass-migration; the push and pull factors as well as the general modus operandi are reviewed. The generally recognised routes; Western Mediterranean, Central Mediterranean and West African which facilitate the migration are assessed. Lastly, the thesis then analyses the compliance of the EAM (Immediate Action) with international law. Each of the Immediate Actions; 1) Saving Lives at Sea 2) Targeting Criminal Smuggling Networks 3) Relocation 4) Resettlement 5) Working in partnership with third countries 6) Using the EU's tools to help frontline are subjected to the relevant international law governing them to test their compliance with international law. Final conclusions of the thesis are then drawn.